Ruminant genetic resources of Rajasthan state: Status, distribution and characteristics - Rahul Behl,; Jyotsna Dhingra Behl,; Anand Jain, (Journal of Livestock Biodiversity, 2025)
Rajasthan is situated in the North-Western region of India having semi-arid to arid environmental conditions. The totalpopulation of ruminant livestock, comprising cattle, buffalo, sheep and goats, in the state is 56.375million. It is home tomany of the important breeds of these species. Despite its tough environmental conditions, the density of ruminants persquare km at 164.72 is more than the national average of 160.15. During 2007-2019, the total cattle and buffalopopulationshave registered an increase of 15 and 23.45 percent, whereas, the sheep and goat populations have shown adecline of 29.37 and 3.08 percent. Between 2007 and 2012, when population of individual breeds of ruminant livestockspecies is available, the populations of pure indigenous cattle, buffalo, sheep and goat have shown a decline of 46.06,53.47, 45.47 and 32.30 percent, respectively. This article attempts to evaluate the present status, distribution andcharacteristics of the ruminant genetic resources of Rajasthan state.